Depressive symptoms and associated factors among older patients with arthritis: evidence from a community-based study in eastern China - Wang, Xinyi; Zhang, Tao; Gu, Xue; Xu, Le; Li, Fudong; Zhai, Yujia; Wu, Mengna; Lin, Junfen (Frontiers in Public Health, 2024)
Abstract Introduction: Depressive symptoms are often experienced by patients with arthritis and are correlated with poor health outcomes. However, the association between depressive symptoms and multidimensional factors (sociodemographic characteristics, health conditions, health behaviors, and social support) among older patients with arthritis in China remains poorly understood. This study aimed to explore the prevalence of depressive symptoms in older patients with arthritis in eastern China and identify the associated factors. Methods: We analyzed data of 1081 older patients with arthritis using secondary data from 2014–2020 from a community-based ongoing study initiated in 2014 in eastern China. The prevalence of depressive symptoms was calculated, and univariate and multilevel logistic regression analyses were used to identify the associated factors. Results: The mean age of older patients with arthritis was 69.16±7.13 years; 42.92% were men and 57.08% were women. The prevalence of depressive symptoms in older patients with arthritis was 14.99% (95% confidence interval: 12.91–17.26%), about 1.8 times higher than that in older adults without arthritis (8.49%, P<0.001). Multilevel logistic regression identified perception of poor economic status (odds ratio [OR]=5.52, P<0.001), multimorbidity (OR=1.96, P=0.001), limitations in activities of daily living (OR=2.36, P=0.004), and living alone (OR=3.13, P=0.026) as factors positively associated with depressive symptoms. Patients diagnosed with arthritis at an older age had lower odds of experiencing depressive symptoms (OR=0.67, P=0.046). Conclusion: Screening for depressive symptoms is essential among older patients with arthritis, especially those who perceive themselves as having a poor economic status, are diagnosed at an earlier age, have multimorbidity, have limitations in activities of daily living, and live alone. The associations of age at arthritis diagnosis and dietary behaviors with depressive symptoms require further research.